Characterization of Volatile Compounds of Bulgur (Antep Type) Produced from Durum Wheat - Saad Ibrahim Yousif; Mustafa Bayram; Songul Kesen (Journal of Food Quality)
Bulgur is enjoyed and rediscovered by many people as a stable food because of its color, flavor, aroma, texture, and nutritional and economical values. There is more than one type of bulgur overall the world according to production techniques and raw materials. The volatile compounds of bulgur have not been explored yet. In this study, Headspace Solid Phase Microextraction (HS-SPME) and Gas Chromatography–Mass Spectroscopy (GS-MS) methods were used to determine the volatile flavor compounds of bulgur (Antep type, produced from Durum wheat). Approaching studies were used and the results were optimized to determine the ideal conditions for the extraction and distinguish the compounds responsible for the flavor of bulgur. Approximately, 47 and 37 important volatile compounds were determined for Durum wheat and bulgur, respectively. The study showed that there was a great diversity of volatiles in bulgur produced using Durum wheat and Antep type production method. These can lead to a better understanding of the combination of compounds that give a unique flavor with more researches.